Improved long‐term survival and renal recovery after acute kidney injury in hospitalized patients: A 20 year experience. Issue 12 (December 2016) - Long, Thorir E.; Sigurdsson, Martin I.; Sigurdsson, Gisli H.; Indridason, Olafur S.
Abstract: Aim: Acute kidney injury (AKI) is a common complication of medical and surgical interventions in hospitalized patients and associates with high mortality. Our aim was to examine renal recovery and long‐term survival and time trends in AKI survival. Methods: Changes in serum creatinine (SCr) were used to define AKI in patients at Landspitali University Hospital in Iceland from 1993 to 2013. Renal recovery was defined as SCr < 1.5× baseline. Results: Out of 25 274 individuals who had their highest measured SCr during hospitalization and an available baseline SCr, 10, 419 (41%) had AKI during hospitalization (H‐AKI), 19%, 11% and 12% with Stage 1, 2 and 3, respectively. The incidence of H‐AKI increased from 18.6 (95% CI, 14.7–22.5) to 29.9 (95% CI, 26.7–33.1) per 1000 admissions/year over the study period. Survival after H‐AKI was 61% at 90‐days and 51% at one year. Comparing H‐AKI patients to propensity score matched individuals the hazard ratio for death was 1.49 (1.36–1.62), 2.17 (1.95–2.41) and 2.95 (2.65–3.29) for Stage 1, 2 and 3, respectively. One‐year survival of H‐AKI patients improved from 47% in 1993–1997 to 57% in 2008–2013 and the adjusted hazard ratio for mortality improved, compared to the first 5‐year period, 0.85 (0.81–0.89), 0.67 (0.64–0.71), and 0.57 (0.53–0.60) for each subsequent 5‐year interval. Recovery of renal function was achieved in 88%, 58% and 44% of patients in Stages 1, 2 and 3, respectively, improving with time. Conclusions: Acute kidney injury is an independent predictor of long‐term mortality in hospitalized patients but there has been a marked improvement in survival and renal recovery over the past two decades. Summary at a Glance: This Icelandic national cohort examines the incidence of acute kidney injury (AKI) amongst hospitalized patients, its impact on outcomes and evolution over time. As expected, AKI predicts mortality, but the trends have improved over the 20‐year study period.